Effects of Back Muscle Strengthening Exercises in Patients with Chronic Non Specific Low Back Pain- A Clinical Trial - Rahman, Md Mahmudur; Rashid, Md Imamur; Shakoor, MA (Medicine Today, 2014)
A randomized clinical trial was done to find out the effects of back muscle strengthening exercises in patients with chronic non specific low back pain (CNLBP). A total of 60 patients were included. They were divided into two groups, control group and interventional group by randomization with the way of lottery. Control group ( Group-B) was treated with non steroidal anti inflammatory drugs (NSAIDs), activities of daily living (ADLs) instructions and warm moist compression. Experimental group ( Group-A) was treated with NSAIDs), activities of daily living (ADLs) instructions, warm moist compression along with back muscle strengthening exercises. Initial evaluation and three follow up visits was given at two weeks, six weeks and twelve weeks. Measurement of pain intensity was performed by Visual Analogue scale (VAS). Student t test and chi-square (X2) test was done to see the level of significance whenever it is necessary. A probability value (p) of less than 0.05 was considered to indicate statistical significance. There was no significant improvement in pretreatment, after 2 weeks and after 6 weeks between two groups. But after 12 weeks follow up exercises group exhibited significant improvement than the control group (P<0.001) So, it can be concluded that back muscle strengthening exercises is effective to improve the patients with CNLBP. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21309 Medicine Today 2014 Vol.26(1): 28-30